Protagonists of Urban Order from the Middle Ages to the Present. - Benyovsky Latin, Irena. Link ([S.l.])
1 online resource
Keywords: European cities and towns are considered places with a particular order established by their inhabitants. This volume centres on the authorities, groups, and individuals who formed the rules for common life in urban communities. It considers the protagonists of urban order between the Middle Ages and modernity: those who were responsible for the common welfare, those who produced change, and those who caused disorder. The authors focus on the practices that shaped the order of urban communities and in particular on situations in which this order was transformed socially and spatially. By looking at urban order through this lens, the volume sheds light on the complex interplay of interests that can bring about change.